Export opportunities in the presence of adjustment costs - Artuc, Erhan (2013)
This paper studies firm behavior and market outcomes that result from new export opportunities in a context of capital adjustment costs and imperfect labor mobility. We develop a dynamic model of firms and workers and estimate its structural parameters using Argentine data. Results uncover quantitatively important complementarities between export opportunities and the ability of firms to react to positive price shocks. These complementarities are comparatively more important in the short run, for small shocks, and related to investment decisions.